Cálculo diferencial integral: aplicações na educação básica - SILVA, Edivaldo Bastos da (Instituto Federal do Amapá, 2021)
This research sought to briefly show some possible applications of Differential and Integral Calculus in Basic Education. Having as generator theme the demonstration of alternatives to introduce the study of Calculus in Basic Education, without compromising the student's learning and increasing the teaching load. The literature review involved both Induction to Calculus and the approach to Calculus in textbooks. The methodology was based on a theoretical survey of some books and scientific articles, related to the proposal's theme, using existing resources in the library of the Federal Institute of Amapá - Campus Macapá, as well as in periodicals, books from its collection and through access to sources available on the internet. Thus, the applications of Calculus in the disciplines of Mathematics, Physics, Biology, Chemistry, among others, were presented in a didactic way, with the purpose of demonstrating and presenting these mathematical tools in an understandable and accessible way to students and teachers, emphasizing that it is not a simple task for the math teacher, but it is possible to arouse interest in calculus when working on issues that are related to the students' experience. In addition, the work sought not only to contribute but also to enrich the research indicators in the area of Calculation for Basic Education, showing different suggestions on the theme.